Ductility, recovery and strain rate dependency of an acrylic structural adhesive. (1st June 2017) - Angelidi, Myrsini; Vassilopoulos, Anastasios P.; Keller, Thomas
Highlights: Different properties resulted for tension and compression at similar strain rates. Increasing the strain rate increased most properties with a logarithmic trend. The acrylic adhesive exhibited high energy-based ductility indices. The time-dependent recovery after unloading was modeled by a Weibull-based model. High recovery after 48 h implied that no residual deformation was caused by damage. Abstract: The ductility and time-dependent recovery of a ductile acrylic adhesive were investigated in this work. The quasi-static true tensile and compressive strain behaviors were examined at different strain rates, taking large deformations into account. Yield stress, elastic modulus, and failure strain exhibited a logarithmic dependency on increasing strain rate, while yield strain and stiffness after yielding were insensitive to strain rate. High energy-based ductility indices were obtained compared to traditional materials. The time-dependent recovery after unloading depended on loading type (tension or compression), the strain rate of loading, and the strain at unloading. The delayed recovered strain development was modeled using an existing Weibull-based model for creep recovery. The strain after unloading almost fully recovered after 48 h, indicating that no residual deformation caused by damage or plastic flow occurred.